LA PRESENZA ITALIANA NELLE ORGANIZZAZIONI INTERNAZIONALI DI GEOMATICA - Selvini, Attilio (GEOmedia, 2014)
The author wonders about the role of Italian in International Organizations of Geomatics and expresses its regrets regarding the current situation of young people apparently do not existing on the international scene, recalling memories and emotions of a famous past that now is fading.